Characterization of Extra- and Intracellular Phytases from Bacteria Proliferating during Tempe Production - Sutardi Sutardi (Indonesian Food and Nutrition Progress, 2003)
Bacteria species Streptococcus faecium and Streptococcus dysgalactiae, proliferating during tempe (fermented soybeans) production produced both extra- and intracellular phytases. The enzymes were isolated from growth media and the cultured bacteria and partially purified by acetone fractionation. Extracellular phytase activities were higher than that of the intracellular enzymes. The extra- and intracellular phytases of S. faecium and S. dysgalactiae acted over a nerrow pH range at 4.1 – 4.3 and the maximum activity at 45", 45", 45", and 40-c, respectively. Among the estimated K values, the value of 1.0 x I Mfor the intracellular phytase of S. dysgalactiae was the lowest, indicating strong affinity of the enzyme for the substrate. V.valties were 0.005 and 0.007 nimole P,. liberated/min/ml enzyme for the extra- and intracellular phytases of S. faeciwn, while the extra- and intracellular phytases of dysgalactiae had V. values of 0.003 and 0.003 nimole P. iberated/min/ml enzyme, respectively. The activation energy for hydrolysis of phytic acid by extra- and intracellular phytases of S. faecium and S. dysgalactiae were calculated by the Arrhenius equation to be 3,400; 3,600; 14,600 and 7,100 cal/mole, respectively.